Magnetic impurity doping induced spin-glass state and short-range zigzag order in the honeycomb iridate Na2IrO3. (1st September 2017) - Cai, W P; Yan, Z R; Liu, R M; Qin, M H; Zeng, M; Lu, X B; Gao, X S; Liu, J-M
Abstract: Based on the modified Heisenberg–Kitaev model, the effects of magnetic substitution on the magnetic properties of the honeycomb-lattice iridate N a 2 I r O 3 are studied using Monte Carlo simulations. It is observed that the long-range zigzag state of the original system is rather fragile and can be replaced by a spin-glass state even for small substitution, well consistent with the experimental observation in Ru-substituted samples (Mehlawat et al 2015 Phys. Rev . B92 134412). Both the disordered Heisenberg and Kitaev interactions caused by the magnetic ion-doping are suggested to be responsible for the magnetic phase transitions in the system. More interestingly, a short-range zigzag order is suggested to survive above the freezing temperature even at high magnetic impurity doping levels.